Harari’s concept of macrohistory: origins of popularity and academic status - Zelenkov, Anatoliy I.; Yahela, Yana A. (Journal of the Belarusian State University. History, 2022)
The unprecedentedly high level of popularity of Y. N. Harari, а professor at the faculty of history of the Hebrew University in Jerusalem, and his main book trilogy, foreground the problem of interpreting and explaining the so-called Hararimania phenomenon, which has become a notable event in the academic community and popular culture of modern Western societies. The purpose of this article is the historical and philosophical reconstruction of the creative evolution of Y. N. Harari with an emphasis on identifying the fundamental meaning and status of his concept of macrohistory in this evolution (process). At the same time, the internal inconsistency of this concept is substantiated, which is largely responsible for the dual nature of its perception and assessments in the mass media and professional academic discussions. The designated goal of the article is achieved through contextual interpretation and the solution of its several basic tasks. Among them: identifying and explaining the most important stages of the professional socialisation of Y. N. Harari, as well as determining the reasons behind his transition from medieval studies to macrohistory; identifying the thematic priorities of Y. N. Harari, special attention is paid to the topic of transformation of homo sapiens into homo deus; characterising the educational role of Y. N. Harari’s concept of macrohistory, in particular, the part of it that is associated with the popularisation of modern science and its futurological potential; carrying out a contextual analysis of Y. N. Harari’s idea about a new humanistic revolution, in the process of which classical ideas about humanism and liberalism must necessarily give way to techno-humanism and the data religion. The novelty of this article is determined by the following circumstances. Though there is extensive debate about the work of Y. N. Harari this article represents one of the first attempts to implement not only a historical, but also a philosophical and conceptual reconstruction of his main ideas set forth in the famous book trilogy. Simultaneously this is one of the first articles to make the analysis of Y. N. Harari’s concept of macrohistory the main focus point. This sets us apart from most of the publications devoted to Y. N. Harari, which are usually presented in the form of short and purely descriptive literary reviews. The article presents a new aspect to consider about the creative evolution of the Israeli historian – the interpretation of the causes and origins of the significant popularity of his ideas and main publications. These include the author’s deep understanding of the specifics of mass consciousness and the way its representatives perceive popular science texts. This subtle and adequate understanding largely explains the emotional figurative language, genre originality and literary style of Y. N. Harari.